Mediastinal teratoma with hydrops fetalis in a newborn and development of chronic respiratory insufficiency - Simončič, Milanka (Radiology and oncology (Ljubljana), 2014)
Background. Mediastinal fetal teratoma can be detected as a mass in the chest during a routine prenatal ultrasound screening. Because of the pressure on mediastinal structures it can be the cause of non-immune hydrops fetalis and polyhydramnion. The development of hydrops fetalis leads to fetal death or premature delivery in most reported cases. Early surgical removal is important, but, the result of treatment depends on the stage of development of mediastinal organs and complications in the postoperative period. Case report. A 31-year-old gravida carrying twins, with spontaneous membrane rupture at 32 weeks gestation underwent urgent caesarean section after antenatal ultrasound revealed severe polyhydramnion and hydrops fetalis in geminus A. The child was intubated immediately after birth due to severe respiratory distress. Ultrasound and X-ray revealed a tumour mass in the right hemithorax. Tumour resection was performed at the age of 7 days. Histology examination revealed an encapsulated immature teratoma. The postoperative course was complicated with respiratory insufficiency which turned into chronic at the age of eight months. Conclusion. This is the fifth reported child with fetal mediastinal teratoma and severe hydrops fetalis that survived the neonatal period. Additional diagnostic search revealed abnormal course of both pulmonary arteries, which was probably one of the main causes of respiratory insufficiency.
Keywords: chronic respiratory insufficiency; diaphragm paralysis; kronična respiratorna insuficienca; mediastinal teratoma; mediastinalni teratom; non-immune hydrops fetalis; novorojenčki